Can Cerebrolysin influence chronic deterioration of spatial learning and memory? - Valousková, V; Francis-Turner, L (Journal of neural transmission. Supplementum, 1998)
Our previous studies showed that the nootropic drug Cerebrolysin, applied immediately after the traumatic or excitotoxic brain lesion influenced spatial learning and memory. Long-lasting ameliorative effect of Cerebrolysin was found after its 4-week-administration, while two-week-treatment had only temporal effect. With the aim to verify the capability of Cerebrolysin to restore chronically deteriorated learning and memory. The drug was applied 4 months after lesioning the rat's CNS. The present study shows that Cerebrolysin restored learning capability of the lesioned rats. Although their spatial memory was improved in comparison to lesion untreated controls, it did not reach the level of intact controls. The effect was more pronounced after the application of 1.25 ml/kg b. w. of Cerebrolysin than after the application of 2.5 ml/kg b. w.
Keywords: Animals; Brain Injuries; Memory Disorders; Rats, Long-Evans; Space Perception; chování zvířat; poranění mozku; poruchy paměti; Nootropic Agents; poruchy učení; Learning Disabilities; nootropní látky; potkani Long-Evans; Male; krysa rodu Rattus; Behavior, Animal; vnímání prostoru; Amino Acids; zvířata; mužské pohlaví; aminokyseliny; Rats